A metalloprotease secreted by an environmentally acquired gut bacterium hinders Borrelia afzelii colonization in Ixodes ricinus - Hodžić, Adnan; Veinović, Gorana; Alić, Amer; Seki, David; Kunert, Martin; Nikolov, Georgi; Sukara, Ratko; Šupić, Jovana; Tomanović, Snežana; Berry, David (Frontiers in Cellular and Infection Microbiology, 2024)
Although the importance of the microbiome in the context of tick biology and vector competence has recently come into a broader research focus, the field is still in its infancy and the complex ecological interactions between the tick residential bacteria and pathogens are obscure. Here, we show that an environmentally acquired gut bacterium has the potential to impair Borrelia afzelii colonization within the tick vector through a secreted metalloprotease. Oral introduction of either Bacillus cereus LTG-1 isolate or its purified enhancin (BcEnhancin) protein significantly reduces B. afzelii burden in the guts of Ixodes ricinus ticks. This effect is attributed to the ability of BcEnhancin to degrade a glycan-rich peritrophic matrix (PM), which is a gut protective barrier essential for Borrelia survival. Our study highlights the importance of the gut microbiome in determining tick vector competence and provides a deeper mechanistic insight into the complex network of interactions between Borrelia, the tick, and the tick microbiome.